2014
DOI: 10.1111/ped.12176
|View full text |Cite
|
Sign up to set email alerts
|

Transverse testicular ectopia

Abstract: Described herein are six cases of transverse testicular ectopia. All patients who underwent orchidopexy at the one pediatric surgical unit between October 2001 and January 2008 were evaluated. The medical records of all patients diagnosed with transverse testicular ectopia were evaluated retrospectively. Five patients (84%) were admitted with a symptomatic right inguinal hernia and empty scrotum on the left side. Only one child (16%) had left-sided hernia and right non-palpable testis (age ranged from 1 month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…To our knowledge, Akin M et al and Yıldız A et al have reported the two largest case-series of TTE so far, each one with six patients [1, 15]. Most cases of TTE described in the literature are diagnosed before the age of 18 and management is targeted to protect fertility and reconstruct a normal anatomy by transferring the testis and repairing any associated anomalies such as inguinal hernias.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, Akin M et al and Yıldız A et al have reported the two largest case-series of TTE so far, each one with six patients [1, 15]. Most cases of TTE described in the literature are diagnosed before the age of 18 and management is targeted to protect fertility and reconstruct a normal anatomy by transferring the testis and repairing any associated anomalies such as inguinal hernias.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Yıldız et al in their study have reported a six-case series with TTE, which is the largest series showing this rare pathology up to our knowledge. [12] CONCLUSION The six-cases reported in this series had unusual clinical histories for crossed testicular ectopia, such as bilateral undescended testes with palpable or nonpalpable testes, inguinal swelling instead of hernia and unsatisfactory impalpable testes treatment. However, the same surgical technique was performed on all cases, and impalpable testes were found in the hernia sacs of all patients.…”
Section: Discussionmentioning
confidence: 92%
“…MRI could allow or confirm the diagnosis of transverse testicular ectopia and eventually show any other associated variants or abnormalities [ 42 , 43 ]. In a case report of an accessory scrotum, Ziegelmann et al found that MRI was capable to define the complex relationships between the accessory scrotum and ano-sphincteric complex, as well as identify associated peritoneal lipoma [ 44 ].…”
Section: Resultsmentioning
confidence: 99%